2021
DOI: 10.1088/1361-6463/ac0d26
|View full text |Cite
|
Sign up to set email alerts
|

What is the important factor affecting microwave absorption performance in corncob-derived carbon/Ni composites?

Abstract: Many factors can affect microwave absorption performance, including impedance matching, attenuation constant, electromagnetic (EM) loss capacity, multi-reflection and scattering and so on. In this work, corncob-derived carbon/Ni composites have been chosen to judge which factor has the greatest influence on the EM absorption behaviors, in which the surface area and pore size have been adjusted by the amount of chemical active additive. Closer impedance matching, larger attenuation constant and stronger EM loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…As shown in figure 7(b), the 833 sample exhibits a thickness stability of RL m ; that is, the RL m exceeds −10 dB at 1.6-10 mm and −20 dB at 1.8-10 mm. Meanwhile, the RL m value of the 811 sample exceeds −10 dB at 1.3-10 mm, which is superior to those in previous works [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The comparison exhibits that constructing multi-interfaces is a new strategy for obtaining microwave-absorbing materials with the merits of being strong, wide, and thin.…”
Section: Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…As shown in figure 7(b), the 833 sample exhibits a thickness stability of RL m ; that is, the RL m exceeds −10 dB at 1.6-10 mm and −20 dB at 1.8-10 mm. Meanwhile, the RL m value of the 811 sample exceeds −10 dB at 1.3-10 mm, which is superior to those in previous works [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. The comparison exhibits that constructing multi-interfaces is a new strategy for obtaining microwave-absorbing materials with the merits of being strong, wide, and thin.…”
Section: Resultsmentioning
confidence: 66%
“…Therefore, hysteresis loss and domain wall resonance are excluded in GHz. If magnetic loss is only excited by eddy current loss, the µ ′′ (µ ′ ) −2 f −1 values should be constant at 2-18 GHz [8,11,14]. Obviously, the µ ′′ (µ ′ ) −2 f −1 values of the 833 sample continuously decrease with increasing f, implying that the magnetic loss is contributed to by natural/exchange resonance at 2-18 GHz.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…It is necessary to clarify the influence of different factors on the final EMW absorption performance, which points the direction for the follow-up design of EWAMs. Li et al [123] chose corncob-derived carbon/Ni (CDC/Ni) composites to study the influences of the graphitization degree, pore size, and surface area on the electromagnetic parameters, impedance matching, attenuation constant, and final EMW absorption performance. The authors indicated that the most important factor affecting the EMW absorption performance was the impedance matching, followed by the electromagnetic loss capability and attenuation constant, and finally the multiple reflections and scatterings of EMWs induced by the 3D structure.…”
Section: Reviewsmentioning
confidence: 99%